Faktor-Faktor Yang Mempengaruhi Persistensi Laba Pada Perusahaan Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022 - Widati, Sari; Wedaswari, Made; Sholati, Frimicia Intan (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This research aims to determine the effect of operating cash flow, debt levels, company size, and book tax differences on profit persistence. The data in this research were obtained from the annual financial reports of financial sector companies in the banking subsector listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample selection method used in this research is the purposive sampling method. The analysis techniques used in this research include descriptive statistical tests, classical assumption tests, and hypothesis tests. The total sample used in this research was 31 companies. The research results show that debt levels have a negative and significant effect on earnings persistence. Book tax differences have a positive effect on earnings persistence. Meanwhile, operating cash flow and company size have no effect on profit persistence.